Organomineral fertilizer based on wood ash in bean cultivation in acidic tropical soil - Rackel Danielly de Souza Alves; Edna Maria Bonfim-Silva; Tonny José Araújo da Silva; Jakeline Rosa de Oliveira; Jholian Maicon Ribeiro-Santos; Luana Aparecida Menegaz Meneghetti (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Organomineral fertilizer using wood ash, an agro-industrial waste, as an organic material has potential in agriculture as an alternative fertilizer. The objective was to evaluate the effects of the use of organomineral fertilizers from wood ash in comparison with conventional mineral fertilization in the cultivation of cowpea in acid tropical soil.